Between Development and Environmental Justice: Tracing the Trail of Ecological Conflict and Environmental Crisis in the Kendeng Mountains - Fahmi Kurniawan; Aman Aman; Danu Agustinova (Marcapada: Jurnal Kebijakan Pertanahan, 2026)
Kendeng, as one of the natural landscapes in Central Java, provides various resources that are used by the community, especially the Sedulur Sikep, in carrying out their daily lives. However, the use of natural resources as raw materials for cement has sparked the Sedulur Sikep community to reject and resist the Semen company. Therefore, the conflict in the Kendeng region has become one of the environmental histories in Indonesia. The objectives of this article are 1) to analyze the historical dynamics of human-environmental relations in the Kendeng Mountains and 2) to analyze the representation of ecological conflict in the Kendeng Mountains as a conflict at the local and national levels. This research uses a qualitative approach with a literature study method by analyzing secondary data derived from journal articles that will be analyzed using synthetic analysis. We carry out this process to map the historical roots of the conflict and identify patterns of environmental injustice in regional development. Based on the literature review, it can be seen that the conflict in the Kendeng region represents an ecological conflict that impacts the lives of local communities. The resistance carried out by the Sedulur Sikep community is not just an ordinary environmental movement but a demand for ecological and spiritual sustainability of the community. This conflict demonstrates that development without a focus on justice and environmental sustainability can result in ecological crisis and social alienation. In response to this problem, the government must evaluate and design an optimal spatial plan to harmonize development.